2020
DOI: 10.56278/tnl.v14i1.1496
|View full text |Cite
|
Sign up to set email alerts
|

Science Education Graduates of a State University from 2008-2018: A Tracer Study

Abstract: This descriptive research determined the extent of employability of science education graduates from 2008-2018 in a state university in the Philippines. The study also ascertained the graduates' retrospective evaluation of the science education program in the aspects of adequacy and relevance.  A total of 49 purposively selected graduates responded to the online survey questionnaire. Results revealed that there is a very high employability rate of the graduates of the university. Their educational experience a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…This was supported by the website of Edukasyon. ph [12] that postgraduates' studies provide more in-depth knowledge about their field, it will help them gain specialized knowledge to advance in their profession, and increase industry expertise, and credibility. Furthermore, SkillsYouNeed.com [13] stated that their current job eats study time, struggles with a budget, and feels burnt out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supported by the website of Edukasyon. ph [12] that postgraduates' studies provide more in-depth knowledge about their field, it will help them gain specialized knowledge to advance in their profession, and increase industry expertise, and credibility. Furthermore, SkillsYouNeed.com [13] stated that their current job eats study time, struggles with a budget, and feels burnt out.…”
Section: Resultsmentioning
confidence: 99%
“…It is basis for continuous improvement, communication learning [11], effective time management is the process of utilizing your time to plan your days so that you can do your work with less effort, and make the most out of your time. By controlling it, you can achieve greater and better outcomes in less time, with no stress [12]. while critical thinking skills has 4.61 which is very important in any profession and crucial to think innovation that will be beneficial to the company or other sectors and this was supported by article of University of the People (2022), by practicing critical thinking, they are allowing themselves not only to solve problems but also to come up with new and creative ideas to do so.…”
Section: Resultsmentioning
confidence: 99%
“…There was one that determined if the degree programs were still effective, adequate, and relevant in responding to the rapid and complex changes (Gines, 2014). Likewise, Reusia et al (2020) ascertained the adequacy and relevance of the BSE Science program through the retrospective evaluation. Ramirez et al (2014) identified if the academic-acquired skills and competencies are aligned to the specializations of graduates.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that one of the biggest problems of teachers nationwide is the learning materials provided by the DepEd. Upgrading the instructional facilities, which includes instructional materials, may be given priority to further develop students' competencies in response to the demands of the new industrial era (Reusia et al, 2020). Furthermore, research-based and commercially viable teaching resources are limited in scientific education.…”
Section: Introductionmentioning
confidence: 99%